High-quality and easy-to-regenerate personal filter - Fraenkl, Max; Krbal, Milos; Houdek, Jakub; Zmrhalova, Zuzana Olmrova; Prokes, Borivoj; Hejda, Petr; Slang, Stanislav; Prikryl, Jan; Ondracek, Jakub; Makes, Otakar; Kostyk, Juraj; Nasadil, Petr; et al. (PloS one, 2022)
Proper respiratory tract protection is the key factor to limiting the rate of COVID-19 spread and providing a safe environment for health care workers. Traditional N95 (FFP2) respirators are not easy to regenerate and thus create certain financial and ecological burdens; moreover, their quality may vary significantly. A solution that would overcome these disadvantages is desirable. In this study a commercially available knit polyester fleece fabric was selected as the filter material, and a total of 25 filters of different areas and thicknesses were prepared. Then, the size-resolved filtration efficiency (40-400 nm) and pressure drop were evaluated at a volumetric flow rate of 95 L/min. We showed the excellent synergistic effect of expanding the filtration area and increasing the number of filtering layers on the filtration efficiency; a filter cartridge with 8 layers of knit polyester fabric with a surface area of 900 cm2 and sized 25 × 14 × 8 cm achieved filtration efficiencies of 98% at 95 L/min and 99.5% at 30 L/min. The assembled filter kit consists of a filter cartridge (14 Pa) carried in a small backpack connected to a half mask with a total pressure drop of 84 Pa at 95 L/min. In addition, it is reusable, and the filter material can be regenerated at least ten times by simple methods, such as boiling. We have demonstrated a novel approach for creating high-quality and easy-to-breathe-through respiratory protective equipment that reduces operating costs and is a green solution because it is easy to regenerate.
Keywords: aerosoly; prostředky na ochranu dýchání; testování materiálů; Equipment Design; Respiratory Protective Devices; COVID-19; Filtration; Humans; polyestery; masky; Masks; lidé; Polyesters; filtrace; Aerosols; design vybavení; Materials Testing